SOCIAL LIFE IN AMERICA - Ahmedov Azimjon Ilhomovich; Jalolov Jasurbek Hayitboy o'g'l (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. From this article we can learn about the society life in America and also their friendship, culture and soon. Americans are hardworking and obsessed with success and material comfort. They believe in equality and freedom, and they hold that love can conquer all.